DEEMED COST: UM ESTUDO DE CASO EM COOPERATIVA MÉDICA - Regina Pagliuso, Silvia; Fernandes Martins, Vidigal; Pagliuso, Ulisses (LINKSCIENCEPLACE, 2016)
This work based on changes caused by Laws 11638/07, Decree 449/08 and Law 11941/09Foi conducted a case study in a medical cooperative mining, analysis of the results were discussedbased on technical accounting pronouncement 27 CPC27, pre pared based on InternationalAccounting Standards (IAS)16. Among therecommendations set by the legislation, the research assessed the criteria forme asurement, recognition and distribution of fixed assets and their implications in usingthese evaluation criteria.